The intrepid parent's field guide to the baby kingdom : adventures in crying, sleeping, teething, and feeding for the new mom & dad - Jennifer Byrne (Adams Media, 2013)
A guide for new parents looks at babies as almost a completely different species and explains how to interpret every sound and move they make, while providing information and observations on all other key stages in their development.